Aplikasi Konsep Manajemen Anti Penyuapan Bagi Organisasi Kristen - Angin, Yakub Hendrawan Perangin; Yeniretnowati, Tri Astuti (Sekolah Tinggi Teologi Kanaan Nusantara, 2024)
Eradicating bribery in business and public services as well as private services is still difficult to eradicate, even in religious organizations there are still people who take bribes. This research discusses the international standard ISO 37001:2016 as a standard that guides efforts to prevent, detect and report bribery practices in organizations, both profit and non-profit, as well as small, medium and large organizations, whether public, government or private organizations, even NGOs and religious organizations. Research method using literature study. The results of this research are how the practice of bribery in the Bible and the world can be minimized by means of understanding, understanding and commitment to implementation from the leadership and management of Christian organizations both at the level of the Director General of Christian Community Guidance, at the level of church associations that oversee various synods, and at the level of church synods. , as well as at the Foundation that oversees Christian Religious Colleges and Christian Schools.AbstrakPemberantasan suap dalam bisnis dan pelayanan publik serta pelayanan swasta masih susah dihapuskan, bahkan di organisasi keagamaan pun suap menyuap masih ada yang melakukan. Penelitian ini membahas standar internasional ISO 37001:2016 sebagai standar yang memandu dalam upaya mencegah, mendeteksi dan melaporkan praktik suap dalam organisasi baik laba maupun nirlaba, serta baik organisasi kecil, sedang maupun besar, apakah organisasi publik, pemerintah maupun swasta bahkan LSM dan keagamaan. Penelitian ini menggunakan metode studi pustaka. Adapun hasil dari penelitian ini adalah bagaimana praktik suap dalam Alkitab dan dunia dapat diminimasi dengan cara pengertian, pemahaman dan komitmen penerapan dari pimpinan serta manajemen organisasi Kristen baik di tingkat Dirjen Bimas Kristen, di tingkat persatuan gereja yang menaungi berbagai sinode, dan di tingkat Sinode gereja, serta di Yayasan yang menaungi